The Effects of Postharvest Losses of Rice on the Income of Rice Farmers in Makurdi Local Government Area of Benue State Nigeria - Okadonye, Emmy Owoicho; Idyorough, Alamveabee Efihraim; Lawrence, Ikyoh Aondoaver (Current Perspectives in Agriculture and Food Science Vol. 1, 2022)
This study examined the effects of postharvest losses of rice on income of rice farmers in Makurdi Local Government Area of Benue State. The study specifically examined the factors responsible for postharvest losses of rice and the effect of postharvest losses of rice on the income of farmers. The modernization theory was adopted as the theoretical framework for the study. A sample of 399 rice producers were drawn in Makurdi using the Taro Yamane formula. Information from respondents was elicited using quantitative data collection techniques. The findings from the study revealed that, several factors were responsible for the postharvest losses of rice including inadequate processing facilities animal/pest attacks, inadequate storage facilities, lack of modern technology, negligence in monitoring rice along the supply chain and lack of educational awareness on postharvest management of rice. The study further revealed that postharvest losses of rice affect the income of the farmers. The study therefore recommended sensitization of farmers through the relevant agricultural agencies on postproduction of rice, establishment of reserves for the preservation of rice, establishment of regulatory body to oversee the market price of rice, linking farmers with agro-processing equipment available in state or those at national research institute at an affordable price, plus farmers to take advantage of cooperatives to benefit from agricultural projects establish by the government.